Indian agriculture in the new millennium : changing perceptions and development policy - Mujumdar, N. A.; Kapila, Uma.; Academic Foundation (New Delhi, India); Indian Society of Agricultural Economics (New Delhi : Academic Foundation, 2006)
Contributed articles on economic aspects of agriculture in India.
"Published by Academic Foundation in collaboration with Indian Society of Agricultural Economics"--P. facing t.p.
Includes bibliographical references.
oif 15/09/15
Loan
Keywords: Agriculture -- Economic aspects -- India